A systematic literature review comparing the psychological care needs of patients with mesothelioma and advanced lung cancer. (December 2016) - Ball, Hannah; Moore, Sally; Leary, Alison
Abstract: Purpose: Psychological distress which adversely affects a person's experience of cancer has been shown to be highly prevalent in patients with mesothelioma. Historically, the assumption has been made that the evidence guiding the supportive care needs for lung cancer is relevant to those with mesothelioma. The objective of the study was to evaluate if the psychological care needs differ between patients with pleural mesothelioma and those with advanced lung cancer. Methods: A search of MEDLINE, CINAHL, PsycARTICLES, Psychology and Behavioural Sciences Collection, PsycINFO databases, grey literature and the Cochrane Library of Systematic Reviews identified 17 studies meeting a predefined inclusion criteria. These were critically appraised for quality. Data relating to psychological experiences was extracted which was then synthesised narratively and through a process of meta ethnography. Results: Common themes identified across the studies created 10 key concepts. These were uncertainty, normality, hope/hopelessness, stigma/blame/guilt, family/carer concern, physical symptoms, experience of diagnosis, iatrogenic distress, financial/legal and death and dying. Key similarities and differences were identified between the mesothelioma and lung cancer evidence. Conclusions: There is limited research exploring the lived experiences of those with mesothelioma and lung cancer, with the majority of them having methodological and/or reporting concerns compromising the conclusions made. However, reoccurring themes in the evidence were found suggesting a number of areas where the psychological experience of mesothelioma differs from that of advanced lung cancer. These findings warrant further research to explore further and if proven, the need for the provision of specialist mesothelioma care services is affirmed. Highlights: There is limited research exploring the lived experiences of those with mesothelioma and lung cancer. Common themes were identified across the 17 studies included in the review, creating 10 key concepts. Reoccurring themes suggests areas where the psychological experience of mesothelioma differs from that of lung cancer. 3 key areas of difference identified between the two groups related to hopelessness, blame and financial/legal issues. These findings warrant further research to explore.